Video-Assisted Thoracoscopic Pleural Biopsy: a Game Changer for Undiagnosed Pleural Effusions (Faridpur Medical College Journal, 2026)
Background: VATS pleural biopsy has emerged as a transformative tool that resolves the long-standing diagnostic uncertainty of pleural effusion by offering a safer, minimally invasive, and far more definitive path.Materials & Methods: This longitudinal descriptive study, conducted at NIDCH in Dhaka over 18 months, enrolled adult patients with undiagnosed pleural effusion using a convenience sampling approach. All eligible participants underwent thorough baseline investigations before the VATS procedure, which was performed under anesthesia through a thoracoscopic incision. Suspicious pleural areas were biopsied and sent for histopathological analysis. The procedure concluded with chest drain placement and meticulous wound closure.Results: The majority of VATS patients had a mean age of 50.9 ± 14.7 years; males accounted for 67.7%. Diabetes and hypertension were each present in 25.8% of patients. Pleural thickening was most frequent (48.4%), followed by pleural nodules (16.1%), while 9.7% showed no visible abnormality. The mean procedure time was 99.06 ± 13.52 minutes, with an average hospital stay of 20.45 ± 19.14 days and a treatment cost of 23,225.81 ± 9,572.39 taka; complications included hydropneumothorax, surgical emphysema, wound infection, and empyema thoracis. Metastatic adenocarcinoma was the most frequent diagnosis (29%), followed by tuberculous pleuritis (19.4%), chronic pleuritis (13%), malignant mesothelioma (3.2%), clear cell carcinoma (3.2%), and a diverse group of other conditions (32.2%).Conclusion: The study revealed that VATS pleural biopsy safely diagnosed a wide variety of conditions while maintaining low complication rates and manageable hospital stays.Faridpur Med. Coll. J. 2026;21(1):12-16